Analisis Pelaksanaan Penyuluhan 3R (Reuse, Reduce, dan Recycle) di SDN 04 Dawuhan Sengon - Ghina Ishmah Tsabitah; Ilun Mualifah (Jurnal Pendidikan Nusantara, 2025)
Waste management in Indonesia is becoming more complicated and is now a serious problem that affects the environment and public health. A lack of awareness and knowledge about proper waste management makes waste a source of loss. This study aims to improve the awareness and skills of elementary school students at SDN 4 Dawuhan Sengon in managing waste through education on the 3R concept (Reduce, Reuse, Recycle). A qualitative method using direct observation and surveys was used to explore students' understanding and behavior regarding waste management. The education sessions involved explaining the principles of 3R and practicing waste sorting based on color and type of bottles, as well as working with waste collectors to ensure waste can be recycled and provides economic benefits. The results showed active student participation in the sorting process and an increase in environmental awareness. This approach is hoped to become an effective model for addressing local waste problems through education and community-based management.